APLIKASI KURSUS KOMPUTER ONLINE MENGGUNAKAN PHP PADA LEMBAGA KURSUS KOMPUTER YOGZ COURSE - Harni Kusniyati; Yoga Hapsara Mursidigama (PETIR, 2015)
Computer course institute Yogz Course is a computer education institution that providecomputer training services. But then, for the time being, the numbers of participant slowly reduced.The reason of this issue is because most of the participants constrainted by travalled distance to thecourse location and not rarely somehow course schedule clashed with other activities. Because ofthat for settling this issue, it is necessary to build an online course application that can be accessedanytime and any where without constrainted by time and distances as long as connected to theinternet. This research goes in a certain direction for producing a simple web based onlinecomputer course application, small, and solid in filling all of the requirement of Yogz Courseinstitution by creating a method of flexible learning and teaching process but still in line with itcurriculum and scoring standard, and also without overrided user friendly element to the end users.To build this application, the method applied is System Development Life Cycle (SDLC), consist ofCommunication (Analysis Requirement), Planning, Modeling, Construction, Deployment. Thisapplication coded with programming languages such as PHP, HTML and CSS, plus MySQL asdatabase. The result of this research is website of Yogz Course online computer course. With thisonline course application, it is expected can give an easy way for course institution in recruitingmore participants and facilitate the participants for going through in learning and teaching processwithout any worry of constrainted by the time and distance as long as internet media available, butstill in line with the curriculum applied by the institution.